Destroying the other's collective memory - Gur-Ze'ev, Ilan (Counterpoints (New York, N.Y.), 2003)
"Destroying the Other's Collective Memory addresses education as the violence that constitutes the passions, conceptual apparatuses, consciousnesses, possibilities, limitations, and aims of subjects and collectives. The mutual quests for control, productivization, and destruction of the Israeli and Palestinian passions, concepts, identities, and potentials are here reconstructed. This reconstruction serves as a test case for counter-education, addressing the challenges of the era of meaninglessness. Referring in detail to the Israeli/Palestinian context, it confronts the wrecking of the modern utopia of nonviolent, democratic public spheres in which a rational, solidarian, and pure human being replaces God. Destroying the Other's Collective Memory challenges our impoverished time, which not only lacks the presence of "God," but lacks the meaning of his absence."--BOOK JACKET.